Factors affecting the individual’s behavior towards Islamic banking: a case study at Bank Rakyat in Jasin / Nor Rauda A Karim - A Karim, Nor Rauda (Faculty of Business and Management, 2015)
The purpose of this study is to determine the factors affecting the individual’s behavior towards Islamic banking. The respondents for this study are among 50 customers of Bank Rakyat in Jasin. This study was design to look on what the individual expect from Islamic banking and what basis individuals moves towards an Islamic bank. Different variables about demographic factor, religious perspectives and bank services was used for the research and random sampling method used for the purpose of data collection. The Pearson correlation coefficient was used to find out relationship among independent variables dependent variable. The result shows that positive and significant relationship between religious perspectives and bank services towards Islamic banking. People who have high education level have better understanding about Islamic banking. There is need a work on awareness of Islamic banking. It can be conclude from this study that bank services is most significant behavior towards Islamic banking.